Investigating the optimum parameters of a negative photoresist to prepare a V-grooved diffraction grating on Si using photolithography and reactive ion etching techniques. Issue 8 (15th April 2021) - Al-Hadeethi, Yas; Al-Mujtabi, A.; Al-Marzouki, Fahd M.; Mahmoud, Alaa Y.; Umar, Ahmad; Abdel-Daiem, A.M.; Ansari, Mohammad Shahnawaze
Abstract: In this study, the deposition parameters of the SU8 2000.5 negative photoresists have been investigated and optimized for the photolithographic technique. Then, applied the inductive coupled plasma reactive ion etching (ICP RIE) to produce V-shaped groove diffraction grating on a silicon substrate. Spin coater (speed: 1000 rpm) was used to coat the photoresist over the Si substrate. The observed photoresist film thickness was measured by ellipsometry and found to be 800 nm. Interestingly, the film exhibited some stability with increasing the spin speed. The thermogravimetric analysis was used to optimize the baking temperature which was found to be 105 °C. Contrast curves were obtained experimentally and used to optimize the exposure energy along with the images obtained from the field emission scanning electron microscopy (FESEM). The optimized energy fluence was found to be 17 mJ/cm 2 . It was interesting to observe that the thickness of the photoresists film was increasing with the elevation of the exposure energy fluence. The FESEM images were used to optimize the ICP RIE etching process and the best etching conditions for the Si substrate were ICP power: 150 W, bias power: 100 W, and SF6 gas flow rate: 32 SCCM (standard cubic centimeters per minute), O2 gas flow: 8 SCCM, and Ar gas flow of 8 SCCM. It is worth to mention that well-defined V-shaped grooves were observed with a depth of 2 μm under the same experimental conditions.